A Tuned Mass Damper with Nonlinear Magnetic Force for Vibration Suppression with Wide Frequency Range of Offshore Platform under Earthquake Loads - Qiong Wu; Wei Zhao; Weiguo Zhu; Rencheng Zheng; Xilu Zhao (Shock and Vibration)
Tuned mass dampers (TMDs) are applied to ensure the safety and stability of offshore platforms; however, linear dampers are effective for a single resonance frequency, providing vibration suppression only within a narrow frequency band. Therefore, this paper proposed a magnetic TMD with two pairs of permanent magnets on both sides of the structures, which can generate a nonlinearly repulsive force, making the magnetic TMD reliable and robust in damping the oscillations of structures with wide frequency range under seismic excitations. A comprehensively numerical and experimental study was processed to investigate the dynamic performances of the proposed magnetic TMD, by application of a 1 : 200-scale prototype of the offshore platform. The results verified that the performance of the magnetic TMD can be significantly improved than that of the linear TMD, meanwhile maintaining high-speed response characteristics. The experimental results indicated that the displacement, acceleration, and frequency responses of the offshore platform can be significantly reduced; furthermore, the evaluation indices showed that the magnetic TMD system is credible in reducing the overall vibration levels and maximum peak values.